FISH SPECIES COMPOSITION IN SEAGRASS BEDS OF TANJUNG MERAH (NORTH SULAWESI), INDONESIA - Syahailatua, Augy (Marine Research in Indonesia, 2011)
Seagrass beds are found along the shore of Tanjung Merah (North Sulawesi, Indonesia). This ecosystem covers approximately 20 hectars, and are well known to support local fisheries. Thalassiahemprichii was the dominant seagrass species at the study site. This study in the given area was aimed to monitor any changes in fish assemblage structure, and examine the function of seagrass beds for marine fish. Fishes were sampled using the small beam trawl in March 2003, April 2004 and September 2005. A total of 137 species belonging to 34 families were identified. Twenty four species were found abundantly in terms of individual numbers, however Apogon margaritophorus and A. hartzfeldii were the most dominant. These two species were permanent resident, indicated by a catch of large number in different stages of life cycle. We also noticed that many adults of A. margaritophorus kept fertilized eggs in their mouths. This evidence also confirmed that seagrass beds function as both spawning and nursery ground for marine fishes. During three yearsÃ¢â¬â¢ monitoring, there was a slightly seasonal variety in fish assemblage structures.